KINDNESS CONTAGIOUS THROUGH COMMUNICATION BETWEEN NEIGHBORS - Leila Mona; Noviari Harman Dipodiwirjo (PalArch’s Journal of Archaeology of Egypt / Egyptology, 2020)
This research discussed the phenomenon of society during a pandemic. The government policy that establishes Large-Scale Social Restrictions (PSBB) has an impact on the closeness of the community. A close relationship leads to altruistic, prosocial behavior as a form of individual social responsibility (Personal Social Responsibility-PSR). One of the characteristics of PSR is contagious. This research is aimed at describe the implementation of these infectious characteristics in people’s lives in the Depok area. This research used a qualitative method, with natural objects in Harjamukti Village, Cimanggis, Depok, West Java. The data collection technique was done by triangulation, namely through observation, interviews and documentation. This research explored the community’s effoNeighborhood Watch Chiefs to make improvements to the environment around them by working to clean up rubbish and roads, painting road fences and back walls of houses, drawing (murals), making parks etc. This research recommended three main findings that are elaborated on and discussed. The three findings are: 1) Intensity of Communication Between Neighbors Generates Kindness Ideas and Actions; 2) The goodness makes people; 3) kindness is contagious.